Diversity of influences on infant feeding strategies in women living with HIV in Cape Town, South Africa: a mixed methods study. Issue 12 (24th October 2013) - Zulliger, Rose; Abrams, Elaine J.; Myer, Landon
Abstract Objective To explore influences on infant feeding intentions and practices in women living with HIV in South Africa. Methods Structured questionnaires were completed by 207 pregnant women and 203 post‐partum women in Cape Town, South Africa. Concurrently, 34 semi‐structured, qualitative interviews explored the influences on infant feeding strategies in women living with HIV. Results Overall, 50% (104) of pregnant women intended to breastfeed and 22% (45) of post‐partum women ever breastfed. Women who breastfed or intended to breastfeed were significantly more likely to have running water in their homes, to have formal housing and to receive advice in support of breastfeeding. Advice from clinic staff was the strongest predictor of breastfeeding [adjusted relative odds (ARO) in pregnant women: 6.87; 95% confidence interval (CI): 2.67, 17.66; ARO in post‐partum women: 4.04; 95% CI: 1.60, 10.19]. Other important influences included previous infant feeding experiences, desires to protect the infant from HIV and involvement of other care providers. Many women also noted that breastfeeding was not feasible due to work commitments and highlighted concerns around the discontinuation of the free provision of infant formula. Conclusion These results suggest that women living with HIV balance complex influences in deciding on their preferred infant feeding strategies. This underscores the need for extensive provider, patient and community education to ensure consistent messaging, while allowing for adaptation to the circumstances of individual mothers.